Metacognitive Awareness of Reading Strategies among EFL High School Students in China - Yang, Li; Sim, Tam Shu (AJELP: Asian Journal of English Language and Pedagogy, 2017)
The teaching of English in China is increasingly focussing on reading (Bao, 2006) and in recent research, metacognitive aspect of reading strategies has been gaining interest in the field of L2 reading (Zhang & Wu, 2009). This study investigates Chinese EFL high school students’ metacognitive awareness of reading strategies and its relationship with students’ actual reading performance. 118 Chinese high school students were involved in the study. Data were collected through the Survey of Reading Strategies (SORS) and one internal school-based reading exam. One bivariate regression test and one multiple regression test through SPSS were applied to examine the relationship between metacognitive awareness of reading strategies and students’ actual reading performance. The results revealed that the metacognitive awareness of reading strategies as measured by SORS was positively associated with students’ actual reading performance. Further individual factor analysis showed that Global strategy was a significant predictor of reading performance. This study proved the significant role of metacognitive awareness of reading strategies in EFL high school students’ reading performance.